Microstructure of practice activities for team and individual sports - Angelina Li San Tan; Jeffrey Fook Lee Low (Termedia Publishing House, 2022)
Purpose Research on the microstructure of practice activities has reported equivocal findings. Limited sports have been included in systematic observations. Playing form activities have not been examined for individual sports. This study scrutinized the amount of time devoted to different activities during practice and refined the usability of playing form and training form for various sports. Methods Systematic observations were conducted in an elite sports school. Youth athletes aged 16-20 years and coaches from 6 different sports (hurdling, archery, field hockey, netball, squash, volleyball) were involved. Practice activities were categorized as playing form, training form, and transition, and compared between sports. Results The proportion of different activities conducted during practice varied for each sport and coach. Hurdlers employed the longest time on transition (43%), squash players utilized the majority of time on playing form (40%), whilst the archers and all 3 team sports athletes consumed most time on training form (51-83%). Representatives of 3 sports did not engage in any playing form activities. Conclusions This study showed that elite coaches are still applying traditional approaches in structuring practice activities. Coaches should employ playing form during practice sessions, but the definition needs to be adapted to encompass multiple sports.